The Transformation of UIN Ar-Raniry Banda Aceh: Opportunities and Challenges for Islamic Higher Education - Fridiyanto Fridiyanto (Ta'dib: Jurnal Pendidikan Islam, 2017)
The transformation of IAIN Ar-Raniry to UIN Ar-Raniry is very interesting to study because of the uniqueness and privilege of UIN Ar-Raniry Aceh located in Nangroe Aceh Darussalam. The existence of UINAR is more than just an educational institution, but within UINAR's body, there is a social history of the Aceh People. After the transformation to UIN, the students are offered with a more diverse study program that is no longer only focused in Islamic studies, UIN Ar-Raniry opens greater access to students from the general public. However, this act of changing into Islamic University went through ups and downs. The idea of changing the IAIN Ar-Raniry became spotlighted by Acehnese community groups. There was a debate in public discussion and argumentation in mass media, and also among UIN Ar-Raniry's academic community. They argued that this kind of act would raise concerns about the loss of Islamic studies after being changed into UIN. In the midst of the worry of the elements of society about the change to UIN, UINAR has proven the worries wrong and remains strong and the change is very influential on UINAR competitiveness.